If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12s + -1(2s + 3) = 65 Reorder the terms: 12s + -1(3 + 2s) = 65 12s + (3 * -1 + 2s * -1) = 65 12s + (-3 + -2s) = 65 Reorder the terms: -3 + 12s + -2s = 65 Combine like terms: 12s + -2s = 10s -3 + 10s = 65 Solving -3 + 10s = 65 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 10s = 65 + 3 Combine like terms: -3 + 3 = 0 0 + 10s = 65 + 3 10s = 65 + 3 Combine like terms: 65 + 3 = 68 10s = 68 Divide each side by '10'. s = 6.8 Simplifying s = 6.8
| 38=20+9g | | 6(6m-6)=-108 | | 4x^2-25=-4x+10 | | x-31+x+43+x=180 | | -8+9a+-16a-17a+-3a=20 | | 11/6=x/11 | | 4x^3-25=-4x+10 | | 4[e+4]=-12 | | 29.96+x=26.95 | | 7a^2+28a-35=0 | | -8a+9a+(-16a)-17a+(-3a)=20 | | 4x-25=-4x+10 | | 6(j-7)-13=43 | | 2x+2(-1)=12 | | 4/7u=28 | | 2(-2)+2y=12 | | 200n=70 | | 204=-x+276 | | 3e^2x+1=9 | | 1.042=x(1-x) | | 9(2p+3)=81 | | 37=5m-63 | | 10c^2-33ct+20t^21= | | -7b-12=-4 | | 116=5v+16 | | (4x+5y)+(2x-11y)= | | 6a^2-15a-1=0 | | (5x-3)(x-2)(x+1)X=0 | | 6x+32=122 | | -11(26x-52)=44(-9x+3) | | 6p*3= | | 48/3=x/4 |